A structural relationship model of factors affecting customer loyalty for retail convenience store businesses in Bangkok, Thailand - Klankaew, Ratana; Panjakajornsak, Vinai (My University, 2017)
The objectives of this research were: 1) to develop and verify the structural relationship model of factors affecting customer loyalty for retail convenience store businesses in Bangkok and 2) to study the influence of perceived service quality (PSQ), perceived price (PP), perceived product quality (PPQ) and customer satisfaction (CS) on customer loyalty (CL). The sample group comprised 400 customers, all of whom were selected on the basis of convenience sampling. A rating scale questionnaire with a reliability score between 0.911 and 0.967 was used as the research tool. The data were analysed using confirmatory factor analysis and causal structural model analysis as inferential statistics. The results revealed that the model fit confirms as appropriate (GFI = 0.956 and RMSEA = 0.035) Causal variables were able to explain the fluctuation in loyalty for Bangkok convenience stores at the rate of 72.9%. This loyalty was directly influenced by CS and PSQ.
Keywords: CS; Customer satisfaction; Perceived price; Perceived product quality; Perceived service quality; PP; PPQ; PSQ; Store's customer loyalty; Thailand's convenience store industry